Syndecan-1 in mechanosensing of nanotopological cues in engineered materials. (February 2018) - Le, Victoria; Lee, Jason; Chaterji, Somali; Spencer, Adrianne; Liu, Yen-Liang; Kim, Peter; Yeh, Hsin-Chih; Kim, Deok-Ho; Baker, Aaron B.
Abstract: The cells of the vascular system are highly sensitive to biophysical cues from their local cellular microenvironment. To engineer improved materials for vascular devices and delivery of cell therapies, a key challenge is to understand the mechanisms that cells use to sense biophysical cues from their environment. Syndecans are heparan sulfate proteoglycans (HSPGs) that consist of a protein core modified with heparan sulfate glycosaminoglycan chains. Due to their presence on the cell surface and their interaction with cytoskeletal and focal adhesion associated molecules, cell surface proteoglycans are well poised to serve as mechanosensors of the cellular microenvironment. Nanotopological cues have become recognized as major regulators of cell growth, migration and phenotype. We hypothesized that syndecan-1 could serve as a mechanosensor for nanotopological cues and can mediate the responsiveness of vascular smooth muscle cells to nanoengineered materials. We created engineered substrates made of polyurethane acrylate with nanogrooves using ultraviolet-assisted capillary force lithography. We cultured vascular smooth muscle cells with knockout of syndecan-1 on engineered substrates with varying compliance and nanotopology. We found that knockout of syndecan-1 reduced alignment of vascular smooth muscle cells to the nanogrooves under inflammatory treatments. In addition, we found that loss of syndecan-1 increased nuclear localization of Yap/Taz and phospho-Smad2/3 in response to nanogrooves. Syndecan-1 knockout vascular smooth muscle cells also had elevated levels of Rho-associated protein kinase-1 (Rock1), leading to increased cell stiffness and an enhanced contractile state in the cells. Together, our findings support that syndecan-1 knockout leads to alterations in mechanosensing of nanotopographical cues through alterations of in rho-associated signaling pathways, cell mechanics and mediators of the Hippo and TGF-β signaling pathways.